Commemorating the Crusading Past in Late Medieval England: The Worksop Priory Tabula. (26th October 2021) - Doherty, James
Abstract: Memory has featured prominently in recent scholarship on the crusades. In particular, the remembrance of crusaders by their descendants and associated ecclesiastical institutions in the high Middle Ages has attracted considerable attention; however, few studies have concentrated on the commemoration of crusaders in the later Middle Ages. This article examines a late fifteenth-century genealogical poem, which was produced for public display on a tablet at Worksop Priory (Nottinghamshire) and contains unique information about members of the Furnival family on the Barons' Crusade (1239–41), in order to explore how and why medieval institutions preserved memories of crusaders into the late Middle Ages. It argues that, although inaccurate in its crusade narrative, the poem provides invaluable insights into the mechanisms of aristocratic family memory in medieval England; and it focuses on the important role of material prompts in the process of commemoration. Specifically, it suggests that an effigy of Sir Thomas de Furnival was erected at Worksop soon after his death away from home in 1241. In the absence of a written record, this cenotaph acted as a prompt to an oral narrative tradition which informed the Worksop poet when he came to compose his genealogical work. This study is, therefore, an analysis of crusade memory, but it is also an examination of the presentation of a crusade narrative to a public audience, an opportunity to unravel the confused history of three crusading brothers, and an attempt to understand the response of a medieval community that had suffered losses in overseas ventures.